EFFECT OF CHOLESTEROL LOADED CYCLODEXTRIN ON SPERM TRAITS, CHOLESTEROL CONTENT AND PROTEIN TYROSINE PHOSPHORYLATION IN CRYOPRESERVED BUFFALO BULL SEMEN - SINGH, NAVDEEP; CHEEMA, R S; KUMAR, A; KAUR, M; DHALIWAL, G S (The Indian Journal of Animal Reproduction, 2016)
The present study evaluated the impact of cholesterol loaded cyclodextrin (CLC) supplementation (4 mg/ml of extender) in Tris-citric acid egg yolk extender on sperm motility, viability, membrane integrity, cholesterol content and tyrosine phosphorylation of buffalo bull spermatozoa. Thirty ejaculates from 6 buffalo bulls were included in this study. In treatment group, In CLC supplemented extended semen, percent motility, viability and hypo-osmotic swelling increased (p
Keywords: Buffalo bull; Cholesterol loaded cyclodextrin; Cryocapacitation; Sperm traits; Tyrosine phosphorylation